DIVERSIDAD CULTURAL, LENGUA DE SIGNOS Y TELEVISIÓN EN ESPAÑA - Francisco Utray ,Esther Gil Sabroso (Fonseca, Journal of Communication, 2023)
This article analyses television in connection with sign language in Spain during years 2010-2012. It is based on published data on the use of sign language in state television after the General Law on Audiovisual Communication imposed obligations on broadcasters in 2010. Most television channels have included sign language in their broadcasts as guided by national and international legislation